2006
DOI: 10.1002/ar.a.20327
|View full text |Cite
|
Sign up to set email alerts
|

β‐lactoglobulin as a potential modulator of intestinal activity and morphology in neonatal piglets

Abstract: Studies were conducted to determine the effects of the whey protein ␤-lactoglobulin (blg) on the intestinal development and intestinal morphology in neonatal piglets. Two trials (5 and 28 days) were conducted on piglets in three separate groups. One group served as a control group while the remaining two were experimental groups based on diets. The two experimental diets were a bovine colostrum powder, one with supplementation with blg and the other without. The control group remained suckling on a sow. All gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…In addition, it has been shown that -Lg enhances intestinal uptake of retinol, triglycerides, and long-chain fatty acids in pre-ruminant calves (Kushibiki et al, 2001), and it has been speculated that this protein may play a role in the absorption and subsequent metabolism of fatty acids. Other possible functions have been described for this whey protein, such as its role in developing passive immunity with IgG (Sutton and Alston-Mills, 2006). Wong and co-workers (1998) demonstrated that this whey protein stimulates normal murine spleen cells proliferation and Igs production.…”
Section: -Lactoglobulinmentioning
confidence: 96%
See 1 more Smart Citation
“…In addition, it has been shown that -Lg enhances intestinal uptake of retinol, triglycerides, and long-chain fatty acids in pre-ruminant calves (Kushibiki et al, 2001), and it has been speculated that this protein may play a role in the absorption and subsequent metabolism of fatty acids. Other possible functions have been described for this whey protein, such as its role in developing passive immunity with IgG (Sutton and Alston-Mills, 2006). Wong and co-workers (1998) demonstrated that this whey protein stimulates normal murine spleen cells proliferation and Igs production.…”
Section: -Lactoglobulinmentioning
confidence: 96%
“…Total whey proteins 5.0-9.0 8.8-10.4 3.7-7.0 -lactoglobulin 3.2-4.0 2.7-5.0 1. Sutton and Alston-Mills, 2006Wong et al, 1998Mcintosh et al, 1995 Lactose synthesis Treatment of chronic stress-induced diseases Anti-cancerigen activity Markus et al, 2002Ganjam et al, 1997Hallgren et al, 2008 Serum albumin Synthesis of lipids Antioxidant activity Anti-cancerigen activity Choi et al, 2002Smith et al, Laursen et al, 1990 Lactoferrin Antimicrobial activity Antifungal activity Anti-proliferative activity Antiviral activity Immunomodulatory activity Anti-thrombotic activity Orsi, 2004Olakanimi et al, 2002Xu et al, 2010Van der Strate et al, 2001Seganti et al, 2004Togawa et al, 2002Quian et al, 1995a Caseinomacropeptide Anti-cariogenic activity Immunomodulatory activity Prebiotic activity Anti-thrombotic activity Oh et al, 2000 ;Kawasaki et al, 1992;1993Otani et al, 1995a1996Azuma et al, 1984Idota et al, 1994Manso et al, 2002 Immunoglobulins Immunomodulatory activity Growth and development Balan et al, 2010Balan et al, 2009 Lactoperoxidase Antimicrobial activity Antiviral activity Immunomodulatory activity deWit & van Hooydonk, 1996Shin et al, 2005Wakabayashi et al, 2007 Hydrolysis with pepsin Bordenave, 2000 o Ovine milk proteins, g Goat milk proteins, a Studies carried out in the bovine peptide…”
Section: Bovine Ovine Caprinementioning
confidence: 99%
“…In addition, it has been shown that b-LG enhances intestinal uptake of retinol, triglycerides, and long-chain fatty acids in pre-ruminant calves [ 27 ], and it has been speculated that this protein may play a role in the absorption and subsequent metabolism of fatty acids. Other possible functions have been described for this whey protein, such as its role in developing passive immunity with IgG [ 28 ]. B-LG is a rich source of Cys, an essential amino acid that appears to stimulate glutathione synthesis, an anticarcinogenic tripeptide produced by the liver for protection against intestinal tumors [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…After early weaning of piglets, due to the decrease in the concentration of lactic acid bacteria in the digestive tract, the pH of the gastrointestinal tract will increase compared with that before weaning, which is likely to cause a decrease in intestinal acidity and the activity of digestive enzymes in the small intestine (45). Coupled with the stress caused by changes in the diet and environment, this is conducive to the proliferation of pathogenic bacteria, resulting in nutritional or pathogenic diarrhea in piglets (46). Li et al showed that reducing the level of E. coli in the gut microbiota can reduce the incidence of diarrhea in piglets (47).…”
Section: Discussionmentioning
confidence: 99%